(untitled) (INTI Nusa Mandiri, 2019)
The development of the world of government today must be balanced with the development of technology today, where administrative processes in the government must be able to collaborate with information technology. Where the process of arranging the letter should not only be done in the village office but can be done anywhere. In arranging a cover letter at the Tomang Urban Village office, the community must take care of a conventional cover letter, namely by visiting the Tomang Urban Village office by carrying a file and queuing with other visitors. If the community does not bring enough documents, the community must return home to complete the document shortcomings. For this reason, the author makes a web-based cover letter information system in Tomang Village. Through the method that has been used, namely waterfall. Because with waterfall the system development can be more structured. A web-based cover letter information system is expected to help the community in speeding up the submission process. The design of this information system is a solution to the problems that have been observed to solve the problems that exist in Tomang Village, especially in the cover letter.